2020
DOI: 10.1103/physrevb.102.144302
|View full text |Cite|
|
Sign up to set email alerts
|

Nonergodic behavior of the clean Bose-Hubbard chain

Abstract: We study ergodicity breaking in the clean Bose-Hubbard chain for small hopping strength. We see the existence of a nonergodic regime by means of indicators as the half-chain entanglement entropy of the eigenstates, the average level spacing ratio, the properties of the eigenstate-expectation distribution of the correlation and the scaling of the inverse participation ratio averages. We find that this ergodicity breaking is different from many-body localization because the average half-chain entanglement entrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…We see that when the trapping potential is as weak as Ω/J ≤ 0.02, r is close to the Wigner-Dyson (Poisson) value in a region of small (large) U/J. This behavior is consistent with the previous work in the absence of the trapping potential [30,34]. As we will see below, the nonergodic behaviors appear in the Poisson distribution regime.…”
Section: A Small Systemssupporting
confidence: 90%
See 2 more Smart Citations
“…We see that when the trapping potential is as weak as Ω/J ≤ 0.02, r is close to the Wigner-Dyson (Poisson) value in a region of small (large) U/J. This behavior is consistent with the previous work in the absence of the trapping potential [30,34]. As we will see below, the nonergodic behaviors appear in the Poisson distribution regime.…”
Section: A Small Systemssupporting
confidence: 90%
“…In this case, nonergodic dynamics have been found in a strongly interacting regime when there is no trapping potential [32,34]. We show that the presence of a weak trapping potential does not break the nonergodic behaviors caused by the large interaction.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Eigenenergy is scaled as ǫ ≡ (E − E min )/(E max − E min ) ∈ [0, 1], then the eigenstates can be chosen around energy targets [48][49][50]. In the random matrix theory, the discrimination between ergodic and non-ergodic regimes can depend on spectral statistics [34,51]. We can capture the statistical features of spectrum by the level spacing ratios [52,53], r n = min(δ n+1 /δ n , δ n /δ n+1 ), where δ n = E n+1 − E n is the nth level spacing and the eigenenergies are arranged in an ascending order.…”
Section: Energy Spectrum Phase Transition and Thermalization Behaviormentioning
confidence: 99%
“…Later, it was found that the large tilt potential can also produce a similar effect to the disorder, resulting in the non-ergodic many-body systems [28][29][30][31], which has been realized in the latest experiments [32]. In addition, the existence of non-ergodic behaviors is also found for a one-dimensional uniform Josephson junction chain at higher energies or weak Josephson coupling [33] and a clean Bose Hubbard chain under weak tunneling strength [34]. Interesting questions thus arise and need to be clarified, e.g., whether there are other factors that can lead to the ergodicity breaking?…”
Section: Introductionmentioning
confidence: 97%